Development of conductive polymer composites from PLA/TPU blends filled with graphene nanoplatelets - Nordin, N.M.; Buys, Yose Fachmi; Anuar, Hazleen; Ani, Mohd Hanafi; Pang, Ming Meng (Elsevier, 2019)
Poly(lactic acid) (PLA) owns some good properties such as biocompatibility, biodegradability and high strength however it brittleness became the drawback for this polymer to be utilised in a broader fields. Thermoplastic polyurethane (TPU) has high strength and toughness with good biocompatibility which can improve the drawback owned by PLA. In this work, PLA/TPU blend were prepared by melt mixing process with the addition of graphene nanoplatelets (GnP). GnP were used as filler for PLA/TPU to tailor the electrical conductivity and mechanical properties of the composites. These properties can be affected by the dispersion state of GnP in the composite, GnP composition and PLA/TPU ratio, which are the main factors to be considered to determine the optimum composition that possess the best performance. The electrical conductivity was tested using resistance meter and showing that the resistivity of the composite started to percolate in the presence of GnP and the percolation threshold change when blend composition change, by showing that at PLA90/TPU10 show the lowest percolation threshold. The localization of GnP in PLA/TPU blend was predicted by calculation of wetting coefficient along with Owen and Wendt equation and it is predicted that GnP preferentially in TPU phase. Elongation at break of the composite increased as the TPU content increased and when GnP were added in PLA50/TPU50 blend, the elongation at break of the blend rise up significantly, hence affect the mechanical properties of PLA/TPU blends.